12th World Universities Wrestling Championship Greco-Roman style - Competition technical analysis - Soygüden, A.; Imamoglu, O. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
PURPOSE: The purpose of this study was to make the 12th World Universities Wrestling Championships Greco-Roman style competition technical analysis. There were 250 participants from 26 countries participating in Corum / Turkey held on 25-30 October 2016. METHODS: The observation form prepared before the competitions with recorded by two researchers, technical analysis of the recordings were obtained. During the competitions, the scores obtained, warnings, winning types, successful techniques recorded in the technical analyze form. In statistical analysis, the percentage distributions for each parameter and match percentage rates were calculated. RESULT: The number of technical points taken for all weight groups in wrestling competitions was 341points. The most number of techniques were 157 with light weight and the maximum numbers of competitions were 38 with light weight group. The highest number of techniques was achieved in lightweight groups with 157 and with the maximum number of matches was made with 38 in the light weight group. The least number of techniques was made with 63 technique in the heavyweight groups and the least number of competitions was made with 18 matches in the heavy weight group was also seen. The highest number of victory was won by score in the heavyweight group (83%); the highest number of victory was won by technical pin in the lightweight group (21%). In the lightweight weight groups have not been winner by pin. The highest score was made with passive punishment point in lightweight group 28%, middleweight group 38% and heavyweight group 33%. The highest scores in the second row were obtained from the techniques of snap down spin behind with 16% at light weight, high dive takedown at 16.5% in middle weight, and move out of the mat and high dive takedown score at 22% in heavyweight groups. CONCLUSION: As a result; the most effective technique in Greco-Roman style given by the referee was passive punishment point in all weight groups. In this case, the wrestlers need to be more active in the bilateral struggle. In particular, it is suggested to fight tempo wrestling with their arms and chest by fighting against each other and struggle in the standing position.